2013
DOI: 10.4238/2013.september.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Association between single nucleotide polymorphisms of the osteoprotegerin gene and postmenopausal osteoporosis in Chinese women

Abstract: ABSTRACT.Osteoporosis is an important and common complex health problem, particularly in postmenopausal women. It is characterized by a reduction in bone mineral density (BMD) and a deterioration of bone microarchitecture with a consequent increase of fracture risk. The osteoprotegerin (OPG) gene is considered to play an important role in the pathogenesis of osteoporosis. We analyzed SNPs of the OPG gene and associations between these polymorphisms and BMD in 399 Chinese postmenopausal women. BMD was quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…1). Finally, a total of 10 studies were enrolled in this meta-analysis 8, 10–15, 2325 , and a total of 12 SNPs with genotyping data in at least one study were meta-analyzed. Supplementary Table 2 listed the detailed information of recruited studies for this meta-analysis, i .…”
Section: Resultsmentioning
confidence: 99%
“…1). Finally, a total of 10 studies were enrolled in this meta-analysis 8, 10–15, 2325 , and a total of 12 SNPs with genotyping data in at least one study were meta-analyzed. Supplementary Table 2 listed the detailed information of recruited studies for this meta-analysis, i .…”
Section: Resultsmentioning
confidence: 99%
“…The OPG gene has been verified as being involved in bone remodeling, bone mineral homeostasis, and bone matrix composition (Liu et al, 2013) neck, and total hip by DEXA. However, to date, no studies have been published that evaluate the relationship of the 1181G>C and 163A>G SNPs of the OPG gene with BMD in patients with T1DM, despite evidence that these polymorphisms are associated with a loss of bone mass (Shang et al, 2013;Song et al, 2013). Our results, following an examination of the OPG polymorphisms in the T1DM group, demonstrate no association with alterations in BMD and bone biomarkers, but revealed that the levels of ionized calcium were increased in carriers of the OPG 1181G>C polymorphism CC genotype, when compared to carriers of the GG+GC genotypes, suggesting that this polymorphism might favor osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the literature indicates that OPG is considered to be one of the most important candidate genes for influencing the pathogenesis of osteopathy (Song et al, 2013;Wang et al, 2013;Guo et al, 2014) particularly in postmenopausal women. It is characterized by a reduction in BMD.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is a progressive skeletal disease manifested by decreased bone mineral density (BMD) and collateral damage to the bone microarchitecture, which can subsequently lead to impaired skeletal strength and elevated susceptibility to fractures. 2 Multiple and varied factors affect bone mineral density (BMD). These have been summarized by Wang et al 3 as nutritional intake factors (eg, calcium and vitamin D, caffeine, alcohol), body weight, physical activity, and exercise.…”
Section: Introductionmentioning
confidence: 99%